Delta-Alpha EEG pattern reflects the interoceptive focus effect on interpersonal motor synchronization - Angioletti, Laura; Balconi, Michela (Frontiers in Neuroergonomics, 2022)
Little is known about how the modulation of the interoceptive focus impacts the neural correlates of high-level social processes, such as synchronization mechanisms. Therefore, the current study aims to explore the intraindividual electrophysiological (EEG) patterns induced by the interoceptive focus on breath when performing cognitive and motor tasks requiring interpersonal synchronization. A sample of 28 healthy caucasian adults was recruited and asked to perform two tasks requiring interpersonal synchronization during two distinct conditions: while focusing on the breath or without the focus on the breath. EEG frequency bands (delta, theta, alpha, and beta band) were recorded from the frontal, temporo-central, and parieto-occipital regions of interest. Significant results were observed for the delta and alpha bands. Notably, higher mean delta values and alpha desynchronization were observed in the temporo-central area during the focus on the breath condition when performing the motor compared to the cognitive synchronization task. Taken together these results could be interpreted considering the functional meaning of delta and alpha band in relation to motor synchronization. Indeed, motor delta oscillations shape the dynamics of motor behaviors and motor neural processes, while alpha band attenuation was previously observed during generation, observation, and imagery of movement and is considered to reflect cortical motor activity and action-perception coupling. Overall, the research shows that an EEG delta-alpha pattern emerges in the temporo-central areas at the intra-individual level, indicating the attention to visceral signals, particularly during interpersonal motor synchrony.